(untitled) (CIPEEX, 2025)
Introduction: Resuscitative endovascular balloon occlusion of the aorta (REBOA) emerged as an alternative to resuscitative thoracotomy in cases of non-compressible hemorrhage. According to the literature, hemorrhagic shock is one of the leading causes of preventable death in trauma victims and, in this context, REBOA allows temporary hemorrhage control and maintenance of central perfusion. In recent years, the technique has advanced with smaller-caliber catheters, the possibility of partial occlusion (p-REBOA) and selective application in different zones of the aorta, aiming to reduce ischemic complications. The study of this subject is relevant for structuring care protocols for severe hemorrhagic shock. Objective: To analyze the evolution of resuscitative balloon occlusion of the aorta (REBOA) techniques in hemorrhagic shock. Methods: This is an integrative literature review based on 10 original articles selected from the Biblioteca Virtual em Saúde (BVS) and PubMed databases. The descriptors “Hemorrhagic Shock,” “Trauma,” “Aorta,” and “Catheterization” were used, with the application of the boolean operator AND. Articles included were free-access, published between 2020 and 2025, in portuguese or english, classified as original and consistent with the topic. Editorials, letters to the editor, case reports, and texts unrelated to the theme were excluded. Results: The analyzed articles demonstrate advances and controversies regarding the use of REBOA. A randomized clinical trial did not show a reduction in mortality, highlighting the influence of time to deployment and trauma system organization. Another study, however, indicates that REBOA, especially in zone 1, may provide survival rates similar to or superior to resuscitative thoracotomy in scenarios of severe shock and traumatic arrest. In the context of pelvic injuries, research shows that the use in zone 3 may reduce distal ischemia. Furthermore, the development of 7F catheters and p-REBOA represents an important advancement to balance hemorrhage control and distal perfusion. Although national and international registries indicate the feasibility of this method, there is a need for better-structured protocols, team training, and logistics. Therefore, the effectiveness of the technique is associated with proper patient selection, rapid deployment, integration with definitive hemostatic methods, and professional preparedness. Conclusions: In summary, REBOA constitutes a promising tool for the management of non-compressible hemorrhagic shock, serving as a bridge to definitive surgical or endovascular control. Its technical evolution, with p-REBOA, 7F catheters, and selective application in different zones, aims to reduce complications and increase safety. However, current results show that its effectiveness is highly dependent on the trauma system and team experience. Thus, broader clinical studies are needed, especially in developing countries, to guide standardized protocols suited to local realities.